EVALUASI PERDA PROVINSI BALI NO. 6 TAHUN 2014 TENTANG PERLINDUNGAN ANAK (STUDI KASUS: ANAK-ANAK PEDAGANG ASONGAN DI DENPASAR) - Maharani, Sang Ayu Putu Dili; Wirantari, I Dewa Ayu Putri; Wijaya, Komang Adi Sastra (CITIZEN CHARTER; Vol 2 No 2 (2022): Administrasi Publik 2022, 2023)
Bali provincial regulation number 6 of 2014 is a policy by the government to regulate about child protection in Bali. This regulation is under the Social Government and several related departments. The research objective the be achieved is how to evaluate the regulation of child protection. This study uses descriptive qualitative methods with data collection, interviews and documentation. The indicator uses to dissect the result of the regional regulation evaluation research are effectiveness, efficiency, adequacy, alignment, responsiveness, and accuracy. The results of this study indicate this regional regulation has not effective, because it cannot reach the targets is written in the constitution. The lack of the equity means there are still many children of hawkers in Denpasar who were employed by their parents. The civil service police unit routinely patrols to certain points with high mobility, it’s activities to reduce children hawkers. Keyword: Local regulation, Child protection, Hawkers, Evaluation